Fireproof and pressure-resistant artificial stone and preparation method thereof

Through the chemical crosslinking of alkenyl cyclic silicone modified brucite powder and vinyl unsaturated polyester resin, combined with alkaline magnesium sulfate whiskers and masterbatches, the existing flame retardant and compressive properties of artificial stone are solved. The problem of insufficient results has achieved efficient fire protection and compression resistance improvement.

CN118496648BActive Publication Date: 2025-02-07GUANGDONG BAOYUN STONE CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410542385.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-02-07
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

The existing artificial stones have shortcomings in flame retardant properties and compressive resistance, which are difficult to meet the needs of widespread applications.

Method used

Alkenyl cyclic silicone modified magnesium hydrazite powder is used for chemical cross-linking with vinyl unsaturated polyester resin, combined with alkaline magnesium sulfate whiskers and masterbatches, and then heat-pressure-resistant artificial stone is prepared by hot pressing and molding. .

Benefits of technology

The flame retardant and compressive properties of artificial stone are significantly improved, forming a stable and dense network structure, enhancing the thermal stability and mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004821323190000051
    Figure BDA0004821323190000051
  • Figure BDA0004821323190000111
    Figure BDA0004821323190000111
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a fireproof and pressure-resistant artificial stone and a preparation method thereof. Alkenyl cyclic organosilicon-modified brucite powder can be chemically cross-linked with vinyl unsaturated polyester resin to form a stable and dense network structure. Magnesium oxide generated by thermal decomposition of brucite can adhere to the surface of the material, absorb smoke and combustibles, and make combustion difficult. The organosilicon element can be decomposed to generate silicon dioxide and other non-combustible or flame-retardant substances during the combustion process, forming an isolation film to prevent oxygen from contacting the combustion products. The carbon-carbon double bonds in the alkenyl cyclic organosilicon-modified brucite powder are opened to participate in the curing process, promote the combination of modified aggregate and resin, and enhance the compactness of the molecular structure. Alkaline magnesium sulfate whiskers are filled in the pores of the brucite powder to generate a synergistic effect, thereby improving the impact resistance and compressive strength of the artificial stone and reducing the cracking tendency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a fireproof and pressure-resistant artificial stone and a preparation method thereof. Background Art

[0002] Artificial stone, as the name suggests, is a stone similar to natural stone produced through artificial processing. It is a new type of composite material made of thermosetting resins such as polyester and fillers, pigments and other additives, injected into metal molds and heated to solidify. It is widely used in commercial decoration, furniture, bathroom products and art processing. At present, the main binders used in the production of artificial stone are polyester resin or polymethyl methacrylate resin. Polymethyl methacrylate resin requires high temperature curing, consumes a lot of energy and is very expensive. At the same time, it is flammable and has insufficient flame retardancy. The products made from it are often low in strength, which affects the widespread use of artificial stone. Therefore, developing an artificial stone with excellent flame retardancy and compressive strength has become a hot topic of research.

[0003] At present, most of the handicrafts on the market are made of natural stone, but their compressive strength and bending strength are far from meeting people's needs. The currently used organic artificial stone is mainly made of fillers such as stone powder and organic resin mixed and solidified. In the production process, in order to improve the impact strength of artificial stone, glass fiber reinforcement is usually added, but this will significantly hinder its pattern forming, uneven mixing of ingredients or fiber burrs on the surface of the product, making it difficult to make products with uniform quality and excellent appearance performance; Chinese patent CN113277811A discloses an artificial stone handicraft made of granite waste and a preparation method thereof. The artificial stone handicraft made of granite waste is made through the steps of granite waste treatment, mixing, vacuum treatment, and curing; by setting the ratio of raw materials, binders and admixtures, the artificial stone reaches the purpose of high strength and good bending resistance, but the flame retardant and fireproof performance has not been significantly improved.

[0004] In the prior art, inorganic flame retardants such as calcium carbonate and brucite are added, which have a certain flame retardant effect. However, the raw materials have strong polarity before modification, hydrophilic and oleophobic surfaces, poor compatibility with polymers, and uneven dispersion during the mixing process, resulting in different interfaces between artificial stone aggregates and polymers, which is prone to stress concentration. At the same time, the flame retardant efficiency is low, and a higher addition amount is required to exert a better flame retardant effect, causing the processing fluidity of the material to deteriorate, resulting in a decrease in the mechanical properties of the product, and even fracture. Therefore, it is necessary to modify the inorganic flame retardant material and cooperate with other flame retardants to exert the flame retardant effect to improve the fire resistance and compression resistance of artificial stone. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a fire-resistant and pressure-resistant artificial stone and a preparation method thereof, and solve the problem that the existing artificial stone panels have poor flame retardancy and pressure resistance.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A fireproof and pressure-resistant artificial stone comprises the following components in parts by weight: 100 parts of vinyl unsaturated polyester resin, 10-70 parts of olefin ring organic silicon modified brucite powder, 2-4 parts of hardener, 1-3 parts of initiator, 0.5-1.5 parts of accelerator, 2-6 parts of basic magnesium sulfate whisker, 5-8 parts of masterbatch and 10-20 parts of deionized water.

[0008] The preparation method of the fireproof and pressure-resistant artificial stone comprises the following steps: adding alkenyl cyclic organosilicon modified brucite powder and deionized water into a powerful mixer, stirring for 3-5 minutes, adding basic magnesium sulfate whisker, continuing to stir for 5-8 minutes, adding vinyl unsaturated polyester resin and hardener, stirring at 35-50°C for 10-20 minutes, then adding initiator and accelerator and continuing to stir for 15-25 minutes, finally adding masterbatch for color adjustment, stirring evenly and transferring to a mold, vibrating and degassing, placing on a hot press for curing and molding, cooling, grinding and polishing to obtain the fireproof and pressure-resistant artificial stone.

[0009] Preferably, the hardener is any one of 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, and tert-amyl peroxy-2-ethylhexyl carbonate.

[0010] Preferably, the initiator is cyclohexanone peroxide or methyl ethyl ketone peroxide, and the accelerator is cobalt naphthenate or cobalt octoate.

[0011] Preferably, the average length of the basic magnesium sulfate whiskers is 6-10 μm, and the average diameter is 0.5-1.0 μm.

[0012] Preferably, the working pressure of the hot press is 5-10 MPa and the working temperature is 50-70°C.

[0013] Preferably, the curing time is 2-5 hours.

[0014] Preferably, the preparation method of alkenyl cyclic organosilicon modified brucite powder comprises the following steps:

[0015] (1) Add 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid and toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, stir evenly, add allyl methacrylate, react at 45-60° C. for 0.5-1 h, add vinyltrimethoxysilane and 2,6-di-tert-butyl-p-cresol, react at 90-105° C. for 2-5 h, cool to room temperature, and concentrate under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker.

[0016] (2) Add brucite powder and ethanol to a reaction flask, stir evenly at a speed of 400-600 r / min, add an alkenyl cyclic organosilicon crosslinking agent, stir to react, and after the reaction is completed, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

[0017] Preferably, in step (1), the ratio of 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid, toluene, allyl methacrylate, vinyltrimethoxysilane, and 2,6-di-tert-butyl-p-cresol is 1 g:

[0018] (0.001-0.003)g: (10-20)mL: (1.05-1.2)g: (1.35-1.5)g: (0.02-0.05)g.

[0019] Preferably, in step (2), the ratio of brucite powder, ethanol, and alkenyl cyclic organosilicon crosslinking agent is 1 g: (25-35) mL: (1.5-2) g.

[0020] Preferably, in step (2), the reaction temperature is 20-35° C. and the reaction time is 30-60 min.

[0021] By adopting the above technical solution, the beneficial effects of the present invention are:

[0022] The invention firstly utilizes 2,4,6,8-tetramethylcyclotetrasiloxane, allyl methacrylate and vinyl trimethoxysilane to undergo a silylation reaction under the action of chloroplatinic acid to obtain an alkenyl cyclic organosilicon crosslinking agent, then utilizes the siloxy groups on the surface of the alkenyl cyclic organosilicon crosslinking agent to react with the hydroxyl groups on the surface of brucite powder to make the alkenyl cyclic organosilicon crosslinking agent closely associated with the surface of brucite powder to obtain alkenyl cyclic organosilicon modified brucite powder, then utilizes the alkenyl groups of the alkenyl cyclic organosilicon modified brucite powder to initiate polymerization with a vinyl unsaturated polyester resin, adds a hardener, an accelerator and the like to cure the mixture, finally adds a masterbatch to adjust the color, and undergoes curing, drying, polishing and the like to obtain a fireproof and pressure-resistant artificial stone.

[0023] The alkenyl groups of the alkenyl cyclic organosilicon modified brucite powder can be chemically cross-linked with the vinyl unsaturated polyester resin to form a stable and dense network structure. The brucite powder releases water through decomposition to reduce the combustion temperature of the material, dilute the combustion gas, block the air, and reduce the smoke density. The decomposed magnesium oxide has a large surface area, adsorbs smoke and combustibles, makes surface combustion difficult, and is conducive to the formation of a surface carbonization layer, prevents the entry of heat and oxygen, and reduces the generation of combustibles. At the same time, it can also dilute and absorb part of the smoke in the outermost combustion product area, so it has a smoke elimination effect; on the other hand, the organosilicon element in the alkenyl cyclic organosilicon cross-linking agent can decompose to produce silicon dioxide and other non-combustible or flame-retardant substances during the combustion process, forming a layer of isolation film to prevent oxygen from contacting the combustion product, thereby playing a flame retardant role; after modification, the brucite powder has good compatibility with the unsaturated resin, and the magnesium oxide decomposed by the heat of the brucite can adhere to the surface of the material, preventing the radiant heat from directly acting on the resin substrate, slowing down the thermal aging degradation of the resin, and improving the thermal stability of the artificial stone.

[0024] The opening of the carbon-carbon double bonds in the alkenyl cyclic organosilicon modified brucite powder participates in the curing process, promotes the combination of the modified brucite powder and the resin, and forms a dense cross-linked network structure. Unsaturated polyester resin is a thermosetting resin, which is very brittle after curing and molding. After adding brucite powder, the mechanical properties of the resin are improved due to the addition of fillers. In addition, the surface of the brucite after surface treatment changes from hydrophilic to lipophilic, which can improve its dispersion in the resin and its compatibility with the resin. At the same time, the alkaline magnesium sulfate whiskers can be filled in the pores of the brucite powder, enhance the density of the molecular structure, improve the adhesion effect between the modified unsaturated polyester resin and the brucite powder, and improve the impact resistance and compressive strength of the finished stone, thereby reducing the possibility of cracking of the artificial stone. DETAILED DESCRIPTION

[0025] The present invention is further illustrated below through the description of specific implementation modes, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of ​​the present invention, but as long as they do not deviate from the basic idea of ​​the present invention, they are all within the scope of the present invention.

[0026] Vinyl unsaturated polyester resin: appearance is transparent light yellow liquid, acid value is 10 mgKOH / g, viscosity is 8 Pa·s (25°C), solid content is 67%, gel time is 8 min (25°C), produced by Jinling DSM Resins Co., Ltd.

[0027] Masterbatch: Brand No. 561521, produced by Golden Dot (Shenzhen) Industrial New Materials Co., Ltd.

[0028] 2,4,6,8-Tetramethylcyclotetrasiloxane, CAS number is 2370-88-9.

[0029] Allyl methacrylate, CAS number is 96-05-9.

[0030] Vinyltrimethoxysilane, CAS number is 2768-02-7.

[0031] Example 1

[0032] (1) Add 15 g of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.03 g of chloroplatinic acid and 225 mL of toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, stir evenly, add 17.1 g of allyl methacrylate, react at 55°C for 0.5 h, add 21 g of vinyltrimethoxysilane and 0.6 g of 2,6-di-tert-butyl-p-cresol, react at 95°C for 3 h, cool to room temperature, and concentrate under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker. The preparation reaction formula is as follows:

[0033]

[0034] (2) Add 10 g of brucite powder and 300 mL of ethanol to a reaction flask, stir evenly at a speed of 500 r / min, add 18 g of an alkenyl cyclic organosilicon crosslinker, react at 25° C. for 50 min, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

[0035] (3) Add 10 g of alkenyl cyclic organosilicon modified brucite powder and 15 g of deionized water into a high-powered mixer and stir for 4 min. Add 2 g of basic magnesium sulfate whisker with an average length of 8 μm and an average diameter of 0.6 μm and continue stirring for 6 min. Add 100 g of vinyl unsaturated polyester resin and 3 g of 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate and stir at 40°C for 15 min. Then add 2 g of cyclohexanone peroxide and 1 g of cobalt cyclohexaneate and continue stirring for 20 min. Finally, add 6 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 6 MPa and a temperature of 60°C for 4 h. After cooling, grinding, and polishing, a fire-resistant and pressure-resistant artificial stone is obtained.

[0036] Example 2

[0037] (1) To a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, 32 g of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.032 g of chloroplatinic acid and 320 mL of toluene were added, and after stirring evenly, 33.6 g of allyl methacrylate was added, and the mixture was reacted at 60° C. for 0.5 h. 43.2 g of vinyltrimethoxysilane and 0.64 g of 2,6-di-tert-butyl-p-cresol were added, and the mixture was reacted at 105° C. for 2 h. The mixture was cooled to room temperature and concentrated under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker.

[0038] (2) Add 25 g of brucite powder and 625 mL of ethanol to a reaction flask, stir evenly at a speed of 600 r / min, add 37.5 g of an alkenyl cyclic organosilicon crosslinker, react at 35° C. for 30 min, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

[0039] (3) Add 25 g of alkenyl cyclic organosilicon modified brucite powder and 20 g of deionized water into a high-powered mixer and stir for 5 min. Add 3 g of basic magnesium sulfate whiskers with an average length of 10 μm and an average diameter of 0.5 μm and continue stirring for 8 min. Add 100 g of vinyl unsaturated polyester resin and 2 g of tert-amyl peroxide-2-ethylhexanoate and stir at 50° C. for 10 min. Then add 1 g of methyl ethyl ketone peroxide and 0.5 g of cobalt octanoate and continue stirring for 25 min. Finally, add 5 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 10 MPa and a temperature of 70° C. for 2 h. After cooling, grinding, and polishing, a fire-resistant and pressure-resistant artificial stone is obtained.

[0040] Example 3

[0041] (1) Add 8 g of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.0024 g of chloroplatinic acid and 160 mL of toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, stir evenly, add 9.6 g of allyl methacrylate, react at 45° C. for 1 h, add 12 g of vinyltrimethoxysilane and 0.4 g of 2,6-di-tert-butyl-p-cresol, react at 90° C. for 5 h, cool to room temperature, and concentrate under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker.

[0042] (2) Add 15 g of brucite powder and 525 mL of ethanol to a reaction flask, stir evenly at a speed of 400 r / min, add 30 g of an alkenyl cyclic organosilicon crosslinker, react at 20° C. for 60 min, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

[0043] (3) Add 40 g of alkenyl cyclic organosilicon modified brucite powder and 20 g of deionized water into a high-powered mixer and stir for 3 min. Add 6 g of basic magnesium sulfate whisker with an average length of 6 μm and an average diameter of 1.0 μm and continue stirring for 5 min. Add 100 g of vinyl unsaturated polyester resin and 4 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 35° C. for 20 min. Then add 3 g of cyclohexanone peroxide and 1.5 g of cobalt octanoate and continue stirring for 20 min. Finally, add 8 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 5 MPa and a temperature of 50° C. for 5 h. After cooling, grinding, and polishing, a fire-resistant and pressure-resistant artificial stone is obtained.

[0044] Example 4

[0045] (1) Add 12 g of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.03 g of chloroplatinic acid and 180 mL of toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, stir evenly, add 14.1 g of allyl methacrylate, react at 50° C. for 1 h, add 17.4 g of vinyltrimethoxysilane and 0.42 g of 2,6-di-tert-butyl-p-cresol, react at 95° C. for 4 h, cool to room temperature, and concentrate under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker.

[0046] (2) Add 5 g of brucite powder and 150 mL of ethanol to a reaction flask, stir evenly at a speed of 550 r / min, add 9 g of an alkenyl cyclic organosilicon crosslinker, react at 30° C. for 45 min, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

[0047] (3) Add 55 g of alkenyl cyclic organosilicon modified brucite powder and 15 g of deionized water into a high-powered mixer and stir for 4 min. Add 5 g of basic magnesium sulfate whisker with an average length of 8 μm and an average diameter of 0.8 μm and continue stirring for 5 min. Add 100 g of vinyl unsaturated polyester resin and 3 g of tert-amyl peroxide-2-ethylhexanoate and stir at 40° C. for 12 min. Then add 2.5 g of cyclohexanone peroxide and 1.2 g of cobalt octanoate and continue stirring for 18 min. Finally, add 6 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 9 MPa and a temperature of 65° C. for 4 h. After cooling, grinding, and polishing, a fire-resistant and pressure-resistant artificial stone is obtained.

[0048] Example 5

[0049] (1) Add 20 g of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.06 g of chloroplatinic acid and 260 mL of toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, stir evenly, add 23 g of allyl methacrylate, react at 55° C. for 1 h, add 28 g of vinyltrimethoxysilane and 0.7 g of 2,6-di-tert-butyl-p-cresol, react at 100° C. for 5 h, cool to room temperature, and concentrate under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker.

[0050] (2) Add 3 g of brucite powder and 95 mL of ethanol to a reaction flask, stir evenly at a speed of 600 r / min, add 5.7 g of an alkenyl cyclic organosilicon crosslinker, react at 35° C. for 50 min, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

[0051] (3) Add 70 g of alkenyl cyclic organosilicon modified brucite powder and 20 g of deionized water into a high-powered mixer and stir for 3 min. Add 4 g of basic magnesium sulfate whisker with an average length of 6 μm and an average diameter of 0.5 μm and continue stirring for 6 min. Add 100 g of vinyl unsaturated polyester resin and 3 g of tert-amyl peroxide-2-ethylhexyl carbonate and stir at 50° C. for 20 min. Then add 2 g of cyclohexanone peroxide and 1.5 g of cobalt cyclohexaneate and continue stirring for 25 min. Finally, add 8 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 10 MPa and a temperature of 50° C. for 3 h. After cooling, grinding, and polishing, a fire-resistant and pressure-resistant artificial stone is obtained.

[0052] Comparative Example 1

[0053] (1) Add 15 g of 2,4,6,8-tetramethylcyclotetrasiloxane, 0.03 g of chloroplatinic acid and 225 mL of toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, add 42 g of vinyltrimethoxysilane and 0.6 g of 2,6-di-tert-butyl-p-cresol, react at 95° C. for 3 h, cool to room temperature, and concentrate under reduced pressure to obtain a product having the structural formula: Cyclic silicone crosslinker.

[0054] (2) Add 10 g of brucite powder and 300 mL of ethanol to a reaction flask, stir evenly at a speed of 500 r / min, add 18 g of a cyclic organosilicon crosslinker, react at 25° C. for 50 min, filter, wash with deionized water, dry and grind to obtain brucite powder modified with a cyclic organosilicon crosslinker.

[0055] (3) Add 10 g of cyclic organosilicon crosslinker modified brucite powder and 15 g of deionized water into a high-powered mixer and stir for 4 min. Add 2 g of basic magnesium sulfate whisker with an average length of 8 μm and an average diameter of 0.6 μm and continue stirring for 6 min. Add 100 g of vinyl unsaturated polyester resin and 3 g of 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate and stir at 40° C. for 15 min. Then add 2 g of cyclohexanone peroxide and 1 g of cobalt cyclohexaneate and continue stirring for 20 min. Finally, add 6 g of masterbatch for color adjustment. After stirring evenly, transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 6 MPa and a temperature of 60° C. for 4 h. After cooling, grinding, and polishing, an artificial stone is obtained.

[0056] Comparative Example 2

[0057] Add 10g of brucite powder and 15g of deionized water to a high-powered mixer, stir for 4min, add 2g of basic magnesium sulfate whiskers with an average length of 8μm and an average diameter of 0.6μm, continue stirring for 6min, add 100g of vinyl unsaturated polyester resin and 3g of 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate, stir at 40°C for 15min, then add 2g of cyclohexanone peroxide and 1g of cobalt cyclohexaneate, continue stirring for 20min, finally add 6g of masterbatch for color adjustment, stir evenly and transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 6MPa and a temperature of 60°C for 4h. After cooling, grinding and polishing, artificial stone is obtained.

[0058] Comparative Example 3

[0059] Add 15g of deionized water and 2g of basic magnesium sulfate whiskers with an average length of 8μm and an average diameter of 0.6μm to a high-powered mixer, continue stirring for 6min, add 100g of vinyl unsaturated polyester resin and 3g of 1,1,3,3-tetramethylbutyl peroxide-2-ethylhexanoate, stir at 40°C for 15min, then add 2g of cyclohexanone peroxide and 1g of cobalt cyclohexaneate, continue stirring for 20min, and finally add 6g of masterbatch for color adjustment, stir evenly and transfer to a mold, vibrate to degas, place on a hot press, and cure at a pressure of 6MPa and a temperature of 60°C for 4h. After cooling, grinding and polishing, artificial stone is obtained.

[0060] Limiting oxygen index test: Cut the prepared artificial stone into 150mm×100mm×6mm test samples, and use an oxygen index meter to test the oxygen index of the sample in accordance with GB / T 2406. Under the specified test conditions, the material can just maintain the minimum oxygen concentration required for the combustion state of the sample in a mixed airflow of oxygen and nitrogen, expressed as the volume percentage of oxygen. Make three groups for each sample and take the average value.

[0061] Table 1 Limiting oxygen index test

[0062] Limiting oxygen index (%) Example 1 25.2 Example 2 29.6 Example 3 32.8 Example 4 36.4 Example 5 38.1 Comparative Example 1 24.7 Comparative Example 2 20.3 Comparative Example 3 18.5

[0063] It can be seen from the test results in the above table that with the increase of the content of alkenyl cyclic organosilicon modified brucite powder, the limiting oxygen index of artificial stone gradually increases. The limiting oxygen index in Example 5 reaches 38.1%, which can meet the flame retardant standard of artificial stone. This is because the alkenyl group of the alkenyl cyclic organosilicon modified brucite powder can produce chemical crosslinking with the vinyl unsaturated polyester resin to form a stable and dense network structure. The brucite powder releases water through decomposition to reduce the combustion temperature of the material, dilute the combustion gas, block the air, and reduce the smoke density. The magnesium oxide generated by decomposition has a large surface area, adsorbs smoke and combustibles, makes surface combustion more difficult, and is conducive to the formation of a surface carbonization layer, preventing the entry of heat and oxygen, and reducing the generation of combustibles. At the same time, the outermost combustion product area can also dilute and absorb part of the smoke, so it has a smoke elimination effect; on the other hand, the organosilicon element in the alkenyl cyclic organosilicon crosslinker can decompose to produce silicon dioxide or other non-combustible or flame-retardant substances during the combustion process, forming a layer of isolation film to prevent oxygen from contacting the combustion material, thereby playing a flame retardant role.

[0064] The brucite powder modified by the cyclic organosilicon crosslinker in Comparative Example 1 does not contain an olefin group and cannot produce chemical crosslinking with the vinyl unsaturated polyester resin, resulting in its dispersibility in the matrix being inferior to that of the embodiment, but brucite can produce synergistic flame retardancy with organosilicon and has good fireproof performance; the brucite in Comparative Example 2 has not been modified in any way, its surface is hydrophilic and oleophobic, its compatibility with the resin is poor, and uneven dispersion is prone to occur, resulting in poor fireproof performance; Comparative Example 3 does not add brucite powder, does not have flame retardant properties, and has the worst fireproof performance.

[0065] Cone calorimeter test: The ignition time and peak heat release rate of the material are tested using a cone calorimeter with an external radiation heat flux of 50kW / m 2 The sample size is 100mm×100mm×8mm. Three groups of each sample are made and the average value is taken.

[0066] Table 2 Cone calorimeter test results

[0067]

[0068] Ignition time refers to the time from when the test sample is exposed to the heat radiation source to when the fire source is ignited by a certain standard under a certain heater heat flux radiation intensity until the continuous ignition phenomenon appears on the surface; from the test results in the above table, it can be seen that with the increase of the content of alkenyl cyclic silicone modified brucite powder, the ignition time of artificial stone is gradually prolonged, indicating that the surface modified brucite powder can have good compatibility with the resin to form a dense composite material.

[0069] The heat release rate refers to the rate at which the test sample releases heat per unit area after ignition under the preset heater heat radiation heat flux intensity. The higher the heat release rate of the material, the faster the thermal cracking rate of the material surface, thereby producing more volatile combustibles, making it easier to ignite the surrounding combustibles, accelerating the spread of flames, and the greater the danger of the polymer in the material. It can be seen from the test results in the above table that the heat release rate of the composite material after adding modified brucite powder is rapidly reduced, and in Example 5 it is only 115.60kW / m 2 This indicates that the modified brucite powder has better compatibility with the resin. The magnesium oxide decomposed by the heat of brucite can adhere to the surface of the material, preventing the radiant heat from directly acting on the resin substrate, slowing down the thermal aging degradation of the resin and improving the thermal stability of the substrate.

[0070] Impact strength test: According to GB / T 2571-1995 standard, a simply supported beam pendulum impact tester is used to apply an impact bending load to the sample to destroy the sample and use the energy absorbed per unit area when the sample is destroyed to measure the impact toughness of the material. The sample size is 80mm×10mm×4mm.

[0071] Bending strength test: According to GB / T 2570-1995, a universal mechanical testing machine is used to apply a three-point bending load to the specimen. The ratio of the bending moment and the bending section modulus at the maximum load is recorded as the bending strength. The specimen size is 170mm×50mm×65mm.

[0072] Table 3 Mechanical properties test

[0073] <![CDATA[Impact strength (kJ / m 2 )]]> Bending strength(MPa) Example 1 2.64 34.51 Example 2 2.82 36.45 Example 3 3.11 39.21 Example 4 3.45 41.78 Example 5 3.26 40.12 Comparative Example 1 2.36 29.24 Comparative Example 2 2.25 28.63 Comparative Example 3 2.03 26.58

[0074] From the test results in the above table, it can be seen that the opening of the carbon-carbon double bond in the alkenyl cyclic silicone modified brucite powder participates in the curing process, promotes the combination of the modified aggregate and the resin, and forms a dense cross-linked network structure. Unsaturated polyester resin is a thermosetting resin, which is very brittle after curing. After adding brucite powder, the toughness of the resin increases due to the addition of fillers, so its mechanical properties are improved. In addition, the surface of the brucite after surface treatment changes from hydrophilic to lipophilic, which can improve its dispersion in the resin and its compatibility with the resin. Therefore, the strength of the artificial stone is improved when subjected to bending stress and impact stress; at the same time, the alkaline magnesium sulfate whiskers can be filled in the pores of the brucite powder, which increases the density of the molecular structure of the artificial stone, thereby enhancing the strength of the artificial stone.

[0075] Compressive strength test: The artificial stone was made into a sample with a size of 20 mm × 20 mm × 10 mm, and the compressive strength test was carried out using an electronic universal testing machine with a loading rate of 5 mm / min.

[0076] Table 4 Compressive strength test

[0077] Compressive strength(MPa) Example 1 98.6 Example 2 104.8 Example 3 115.2 Example 4 120.3 Example 5 112.6 Comparative Example 1 86.4 Comparative Example 2 85.5 Comparative Example 3 78.2

[0078] The above disclosure is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, any equivalent changes made according to the claims of the present invention are still within the scope of protection covered by the present invention.

Claims

1. A method for preparing fireproof and pressure-resistant artificial stone, characterized in that: The fireproof and pressure-resistant artificial stone comprises the following components in parts by weight: 100 parts of vinyl unsaturated polyester resin, 10-70 parts of olefinic cyclic organosilicon modified brucite powder, 2-4 parts of hardener, 1-3 parts of initiator, 0.5-1.5 parts of accelerator, 2-6 parts of basic magnesium sulfate whisker, 5-8 parts of masterbatch and 10-20 parts of deionized water; The preparation method comprises the following steps: adding alkenyl cyclic organosilicon modified brucite powder and deionized water into a powerful mixer, stirring for 3-5 minutes, adding basic magnesium sulfate whisker, continuing to stir for 5-8 minutes, adding vinyl unsaturated polyester resin and hardener, stirring at 35-50° C. for 10-20 minutes, then adding initiator and accelerator and continuing to stir for 15-25 minutes, finally adding masterbatch for color adjustment, stirring evenly and transferring to a mold, vibrating and degassing, placing on a hot press for curing and molding, cooling, grinding and polishing to obtain fireproof and pressure-resistant artificial stone; The preparation method of the alkenyl cyclic organosilicon modified brucite powder comprises the following steps: (1) Add 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid and toluene to a reaction flask equipped with a reflux condenser, a dropping funnel and a thermometer, stir evenly, add allyl methacrylate, react at 45-60°C for 0.5-1h, add vinyltrimethoxysilane and 2,6-di-tert-butyl-p-cresol, react at 90-105°C for 2-5h, cool to room temperature, and concentrate under reduced pressure to obtain an alkenyl cyclic organosilicon crosslinker; (2) Add brucite powder and ethanol to a reaction flask, stir evenly at a speed of 400-600 r / min, add an alkenyl cyclic organosilicon crosslinker, stir to react, and after the reaction is completed, filter, wash with deionized water, dry and grind to obtain alkenyl cyclic organosilicon modified brucite powder.

2. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: The hardener is any one of 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, and tert-amyl peroxy-2-ethylhexyl carbonate.

3. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: The initiator is cyclohexanone peroxide or methyl ethyl ketone peroxide, and the promoter is cobalt naphthenate or cobalt octoate.

4. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: The basic magnesium sulfate whiskers have an average length of 6-10 μm and an average diameter of 0.5-1.0 μm.

5. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: The working pressure of the hot press is 5-10 MPa, and the working temperature is 50-70°C.

6. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: The curing time is 2-5 hours.

7. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: In the step (1), the ratio of 2,4,6,8-tetramethylcyclotetrasiloxane, chloroplatinic acid, toluene, allyl methacrylate, vinyltrimethoxysilane, and 2,6-di-tert-butyl-p-cresol is 1 g: (0.001-0.003) g: (10-20) mL: (1.05-1.2) g: (1.35-1.5) g: (0.02-0.05) g.

8. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: In the step (2), the ratio of brucite powder, ethanol, and alkenyl cyclic organosilicon cross-linking agent is 1 g: (25-35) mL: (1.5-2) g.

9. The method for preparing fireproof and pressure-resistant artificial stone according to claim 1, characterized in that: In the step (2), the reaction temperature is 20-35° C. and the reaction time is 30-60 min.

Citation Information

Patent Citations

  • Artificial stone artware prepared from agglomerated stone waste residues and preparation method of artificial stone artware

    CN113277811A

  • Artificial solid plane materiel and manufacturing method thereof

    CN103396040A

  • High-strength man-made quartz plate and preparation method thereof

    CN103833265A